2001
DOI: 10.1161/01.hyp.37.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Type A Receptor Blockade Attenuates the Hypertension in Response to Chronic Reductions in Uterine Perfusion Pressure

Abstract: Abstract-A chronic reduction in uterine perfusion pressure in pregnant rats is associated with a significant elevation in mean arterial pressure (MAP) and reduction in kidney function. The purpose of this study was to examine the role of endothelin in mediating the hypertension in response to chronic reductions in uterine perfusion pressure in conscious, chronically instrumented, pregnant rats. MAP in pregnant rats with chronic reductions in uterine perfusion pressure (123.0Ϯ1.8 mm Hg) was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 32 publications
7
133
1
Order By: Relevance
“…There is also evidence that ET-1, via ET A receptor activation, causes hypertension observed in pregnant rats and pre-eclamptic women with chronically reduced uterine perfusion pressure. 24,25 Pharmacological studies confirm the important role of the ET A receptor in BP regulation. Selective ET A antagonists such as BQ 123, BMS 182874 and FR 139317 block the rise of BP in certain rat models, which shows that hypertension is to some extent dependent on endothelin-related mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…There is also evidence that ET-1, via ET A receptor activation, causes hypertension observed in pregnant rats and pre-eclamptic women with chronically reduced uterine perfusion pressure. 24,25 Pharmacological studies confirm the important role of the ET A receptor in BP regulation. Selective ET A antagonists such as BQ 123, BMS 182874 and FR 139317 block the rise of BP in certain rat models, which shows that hypertension is to some extent dependent on endothelin-related mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…18,19 Pregnant rats developed hypertension and increased circulating ET-1 levels when subjected to chronic reductions in uteroplacental perfusion pressure. 20 This hypertension was abolished by selective blockade of the ET-1 type A receptor. Exposure of human umbilical vein endothelial cell cultures to sera collected from reductions in uteroplacental perfusion pressure was followed by an increase in the ET-1 concentration in the media, whereas no such increase was noted when cells were exposed to sera from normal pregnant rats, suggesting that a substance present in the PE sera induced ET-1 synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…48 Using an RNase protection assay, they found that renal expression of preproendothelin was significantly elevated in both the medulla and the cortex of pregnant rats with chronic reductions in uterine perfusion pressure (RUPP) compared with control pregnant rats. Moreover, they reported that chronic administration of the selective ET A receptor antagonist, ABT627 markedly attenuated the increase in mean arterial pressure in pregnant rats with RUPP.…”
Section: Endothelinmentioning
confidence: 99%